Respuesta :

The transformed equation y = -(x - 2)^2 - 3 compared to the parent function involves  translating the parent function to the right by 2 units, reflecting the function across the y-axis and translating the function 3 units down

How to compare the function to its parent function?

The equation of the transformed function is given as:

y = -(x - 2)^2 - 3

While the equation of the parent function is given as

y = x^2

Start by translating the parent function to the right by 2 units.

This is represented as:

(x, y) = (x - 2, y)

So, we have:

y = (x - 2)^2

Next, reflect the above function across the y-axis

This is represented as:

(x, y) = (-x, y)

So, we have:

y = -(x - 2)^2

Lastly, translate the above function 3 units down

This is represented as:

(x, y) = (x, y - 3)

So, we have:

y = -(x - 2)^2 - 3

Hence, the transformed equation y = -(x - 2)^2 - 3 compared to the parent function involves  translating the parent function to the right by 2 units, reflecting the function across the y-axis and translating the function 3 units down

Read more about function transformation at:

https://brainly.com/question/8241886

#SPJ1